2018
DOI: 10.1128/jvi.00908-17
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Genome-Wide Analyses on Our Understanding of Human Herpesvirus Diversity and Evolution

Abstract: Until fairly recently, genome-wide evolutionary dynamics and within-host diversity were more commonly examined in the context of small viruses than in the context of large double-stranded DNA viruses such as herpesviruses. The high mutation rates and more compact genomes of RNA viruses have inspired the investigation of population dynamics for these species, and recent data now suggest that herpesviruses might also be considered candidates for population modeling. High-throughput sequencing (HTS) and bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
110
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 119 publications
1
110
0
3
Order By: Relevance
“…http://dx.doi.org/10.1101/262055 doi: bioRxiv preprint first posted online Feb. 8, 2018; MV than others (Figure 6). This could be indicative of mixed viral populations or changes in polymerase fidelity (24,22). As in congenital HCMV infections (25,28,30), these data suggested that patients experiencing neonatal infection with HSV-2 may harbor mixed or diverse viral populations that are distinct from those observed in adult infections.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…http://dx.doi.org/10.1101/262055 doi: bioRxiv preprint first posted online Feb. 8, 2018; MV than others (Figure 6). This could be indicative of mixed viral populations or changes in polymerase fidelity (24,22). As in congenital HCMV infections (25,28,30), these data suggested that patients experiencing neonatal infection with HSV-2 may harbor mixed or diverse viral populations that are distinct from those observed in adult infections.…”
Section: Discussionmentioning
confidence: 91%
“…There is growing evidence that most herpesviruses contain significant genetic variation, including HSV-1 and HSV-2 (19,22,50,51,64,65). The potential contributions of viral genetic variation to clinical disease in neonates therefore warrants…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include sequencing only mRNAs loaded onto ribosomes (11,12) or the use of specific adaptors to generate sequencing libraries limited to full-length polyadenylated RNAs (13). Lastly, it is important to keep in mind that technical and analytical requirements for transcriptome studies are different from those of genomic studies that might characterize new viruses, detect low frequency variants, or trace the origins and consequences of sequence diversity within populations (14).…”
mentioning
confidence: 99%